Location assessment, relocation and firm performance - Erik Louw; Sylvia Jansen (European Regional Science Association (ERSA), 2010)
Most studies on firm relocation focus on firms that did relocate. The reasons why they moved and why they settled somewhere else, are always seen as the location factors. The assumption behind this is that firms which did relocate assessed their former location unfavourable compared to their production requirements, while firms that did not relocate were more favourable to their location. By means of longitudinal panel survey data on firms in the Netherlands we investigate whether this assumption is valid. First we focus on the location assessment and investigate which location factors are most important in the overall assessment. Next we analyse changes of the location assessment over time. Secondly we analyse stated and revealed relocations in relation to the locations assessment and firm performance (measured in the level of employment). This paper concludes with a discussion on the notion of location factors. Particularly we will focus on their role in the relocation decision process which basically is a matching process between spatial production requirements put forward by firms and locational properties and characteristics of productions sites
Keywords: 330